MODEL KEPEMIMPINAN SEKOLAH KELAS MENENGAH MUSLIM DI YOGYAKARTA - Imam Machali (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2018)
AbstractSchool principal is the important key in leading Islamic educational institutions to improve and develop to be chosen by Islamic middle-class society as a place to educate their children. This research aimed to observe the leadership model of Islamic Senior High School Principal in Yogyakarta in improving, developing, and preserving the quality of Islamic educational institutions to be chosen by Islamic middle-class society in Yogyakarta. The results in this research explained that the leadership model in Islamic Senior High School is transformational leadership. This leadership model is established through two abilities possessed. First ability is knowledgeable, which means that a school principal is knowledgeable about the organizational theories, the organizational culture, the strategic management, the leadership, and other managerial knowledges.Â  The wider knowledge and perspective a school principal has, the more open, flexible, inclusive, and open-minded the school principal is, to be able to manage a new knowledge. Second ability is experience, which is something that someone has encountered, undergone, endured, and borne. Experience is highly related with the ability and the will to continuously learn. The more opportunity to learn, the more experience will be achieved. The combination of knowledge and experience will establish a transformational leadership.Â Abstrak Kepala sekolah menjadi faktor kunci dalam membawa peningkatan dan perkembangan lembaga pendidikan Islam, sehiangga menjadi pilihan masyarakat kelas menengah Muslim untuk menyekolahkan pura putrinya. Penelitian bertujuan melihat bagaimana model kepemimpinan kepala sekolah kelas menengah muslim Yogyakarta dalam upaya meningkatkan, mengembangkan dan menjaga mutu lembaga pendidikan Islam sehingga menjadi sekolah pilihan masyarakat kelas menengah muslim di Yogyakarta. Hasil penelitian menunjukkan bahwa model kepemimpinan sekolah kelas menengah muslim adalah kepemimpinan transformasional. Model kepemimpinan ini terbentuk melalui dua kemampuan yang dimiliki yaitu, pertama, penguasaan pengetahuan (knowledge) seperti teori-teori organisasi, budaya organisasi, manajemen strategic, kepemimpinan, dan pengatahuan managerial lainnya. Semakin luas pengetahuan dan wawasan seseorang pemimpin, maka semakin terbuka, fleksibel, inklusif, mudah menerima masukan (open minded), dan mampu mengolahnya menjadi pengetahuan baru. Kedua adalah pengalamannya. Pengalaman adalah sesuatu yang pernah dialami, dijalani, dirasakan, ditanggung. Pengalaman sangat berhubungan dengan kemampuan dan kesediaan untuk terus belajar. Semakin banyak belajar, maka semakin banyak pula pengalaman yang akan didapat. Penggabungan antara pengetahuan dan pengelaman inilah yang akan membentuk kepemimpinan transformasional.